2003
DOI: 10.1007/s00198-003-1412-5
|View full text |Cite
|
Sign up to set email alerts
|

Incident vertebral fractures and mortality in older women: a prospective study

Abstract: Older persons who have prevalent vertebral fractures have an increased risk of mortality. It is not known whether incident vertebral fractures are also associated with an increased risk of mortality. To determine whether older women with incident vertebral fractures have an increased risk of mortality, we conducted a prospective cohort study of 7233 community-dwelling older women aged 65 years or older who were enrolled in the Study of Osteoporotic Fractures. We measured incident vertebral fractures by radiogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
288
3
24

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 370 publications
(320 citation statements)
references
References 19 publications
5
288
3
24
Order By: Relevance
“…Other studies reported that increased mortality after hip and vertebral fractures was consistent over the initial five-year period. (4,6,8,11) In the present study, prevalent morphometric vertebral deformity and prevalence of hip fracture were not associated with increased mortality. Inconsistency between our report and many previous studies can be explained by differences between incidence and prevalence of fracture, because prevalent vertebral deformity and hip fracture in our study included those cases that had developed many years in the past.…”
Section: Journal Of Bone and Mineral Researchcontrasting
confidence: 39%
See 1 more Smart Citation
“…Other studies reported that increased mortality after hip and vertebral fractures was consistent over the initial five-year period. (4,6,8,11) In the present study, prevalent morphometric vertebral deformity and prevalence of hip fracture were not associated with increased mortality. Inconsistency between our report and many previous studies can be explained by differences between incidence and prevalence of fracture, because prevalent vertebral deformity and hip fracture in our study included those cases that had developed many years in the past.…”
Section: Journal Of Bone and Mineral Researchcontrasting
confidence: 39%
“…M any studies have shown increased fracture risk (1)(2)(3) and mortality (4)(5)(6)(7)(8) after clinical vertebral fracture. Even subjects with no clinical fracture and little pain but with vertebral deformity detected by X-ray showed slightly increased mortality.…”
Section: Introductionmentioning
confidence: 98%
“…Vertebral compression fractures (VCF) constitute a major health problem affecting more than 1.4 million people each year worldwide [1], leading to pain, significant morbidity [2,3], and healthcare expenses [4]. Non-surgical management (NSM) may not relieve pain, frequently leads to prolonged immobilization, and may lead to pulmonary deterioration, persistent pain, progressive kyphotic deformity, weight loss, depression, and overall compromise in life quality [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with VCF are prone to new adjacent fractures (a fivefold increase in risk) [7]. In one prospective study, elderly women with at least 1 VCF had an age-adjusted increased risk of mortality of 32 %; survival impact was more profound with greater numbers of vertebral fractures [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thereby, bedsores may appear (often associated to infections), deep venous thrombosis, decrease of bone mineral density and muscle hypotonia. Other severe effects are mood impairment, depressive syndrome and, finally, higher mortality rate, as demonstrated by various studies [10][11][12][13]. Patients undergoing conservative treatment may also suffer serious consequences related to bracing incontinence [7,14], represented by progressive kyphosis as a result of multiple vertebral collapses, that can potentially lead to thoracic and abdominal visceral compression with severe systemic pathological manifestations.…”
Section: Introductionmentioning
confidence: 99%